An efficient Model Predictive Control-based motion cueing algorithm for the driving simulator. (November 2016) - Fang, Zhou; Kemeny, Andras
Recently, a new technique using a MPC (Model Predictive Control)-based motion cueing algorithm has been successfully applied in driving simulation. However, the feasibility and the stability condition of MPC, a crucial criterion for high-performance simulators, has barely been addressed except in our previous works and in Dagdelen et al. (Model-based predictive motion cueing strategy for vehicle driving simulators. Contr Eng Pract 2009; 17: 995–1003). In this paper, it is shown that based on an implicit MPC algorithm using qpOASES, the authors' proposed feasibility and stability condition not only guarantees the feasibility and stability of the MPC-based motion cueing algorithm, but also controls washout motion, taking into account the driver's perception threshold, thus resulting in a more robust and flexible motion cueing algorithm and a better motion feeling than that for the conventional motion cueing algorithms.